COMPARISON ANALYSIS OF VILLAGE GOVERNMENT WORKLOAD BEFORE AND AFTER PANDEMIC PERIODIN MEKAR JAYA VILLAGE - iyan tuli; rizal rizal; sukrianto sukrianto (Journal of Economic, Business, and Administration (JEBA), 2022)
The research goals are as follows: 1) To ascertain the physical strain associated with completing work in the Mekar Jaya Village Government, Wonosari District, Boalemo Regency, prior to and following the pandemic period. 2) To ascertain the psychological stress associated with completing tasks prior to and following the pandemic in the Mekar Jaya Village Government, Wonosari District, Boalemo Regency. 3) To ascertain the time commitment required to complete activities before and after the pandemic in the Mekar Jaya Village Government, Wonosari District, Boalemo Regency.This is a descriptive study with a qualitative methodology. The researcher employs the descriptive technique because, according to the researcher's character and purpose, he seeks not to test hypotheses but to gain an accurate picture.The findings indicated that 1) the physical burden imposed on the Mekar Jaya village apparatus in completing the work prior to the pandemic had no effect on both the physiological and biomechanical burdens, and 2) following the pandemic, the physiological, physical burden and biomechanical burden imposed on the Mekar Jaya village government remained unchanged. 2) The mental strain placed on the Mekar Jaya village apparatus by finishing work ahead of schedule does not impair focus; in fact, it fosters a sense of bewilderment, vigilance, and correctness in the Mekar Jaya Village Government. Following the epidemic, it was discovered that attention is impaired, even confusing when completing duties, a lack of alertness at work and services that take a long time is not accurate. 3) The mental strain on the Mekar Jaya village apparatus in performing work prior to the pandemic, the pace with which work is completed, and the ability to perform two or more occupations concurrently are all still intact. Meanwhile, following the epidemic, work was frequently completed late, and the Mekar Jaya village machinery could not complete two or more jobs concurrently. Particularly with the 1-day, 1-month aim in mind.